Efficacy and safety of intense pulsed light with a KTP filter for the treatment of solar lentigines. Issue 6 (25th January 2019) - Friedmann, Daniel P.; Peterson, Jennifer D.
Abstract : Background: Optical energy‐based devices, including intense pulsed light (IPL) and potassium titanyl phosphate (KTP) lasers achieve reduction of pigmented and vascular lesions in a relatively similar number of treatments. This study aimed to evaluate the efficacy and safety of an IPL with a "KTP‐like" filter emitting a wavelength of 525–585 nm for the treatment of solar lentigines on the hands and face. Methods: This was a single center, prospective, open‐label clinical trial including 16 healthy Caucasian subjects (15 females, mean age, 55 years; skin types II and III) with hand and facial solar lentigines. Subjects were treated with three IPL treatment sessions with a KTP‐like filter conducted at monthly intervals. Follow‐up evaluations were performed 1, 3, and 6 months after the last treatment session. Overall pigmentation improvement, pigmentation clearance per lesion, adverse events, and subject tolerability to treatment were evaluated. Results: Significant improvements in facial and hand pigmentation were noted at all follow‐up visits ( P < 0.0001). One month after the last treatment session, good to excellent outcomes were noted in 74.6% of treated facial areas and 90% of treated hand regions. Although the effect of treatment gradually declined in both treatment regions over the 6‐month follow‐up period, over 60% of subjects demonstrated good to excellent results at the study end. Clinical effectiveness was further confirmed by the reduction in Melanin Index (MI) following each treatment as compared to baseline. Downtime and complications were minimal. Conclusions: IPL treatment with a KTP‐like filter is a well‐tolerated and effective method for reducing facial and hand pigmentation. Lasers Surg. Med. 51:500–508, 2019. © 2019 Wiley Periodicals, Inc.